2019
DOI: 10.1021/acs.jpcc.9b02795
|View full text |Cite
|
Sign up to set email alerts
|

Internal and External Transport of Redox Species across the Porous Thin-Film Electrode/Electrolyte Interface

Abstract: Transport of redox species (VO2+/VO2 +, V2+/V3+, Ti3+/Ti4+, and Fe2+/Fe3+) across the electrode/electrolyte interface is investigated in a thin-film rotating disk electrode configuration using electrochemical impedance spectroscopy (EIS). The transport features depend on the constituents of the thin-film catalyst layer and on the rate constant of the redox reaction. On Nafion-free porous electrodes, semi-infinite linear and finite transport features are observed under static and hydrodynamic conditions of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 40 publications
2
35
0
Order By: Relevance
“…19 Recently, we reported the transport mechanism of redox species across the porous thin-lm electrode/electrolyte interface and explained the conditions in which either W s element or (R 2 , Q 2 ) elements should be used to t the nite transport feature. 30 Similar EIS features with equimolar concentration of V 4+ /V 5+ redox species at EP are reported in the literature. 29,41,42 However, several others have reported such features (one semi-circle and $45 line) by recording EIS even at measured OCP or at some nite overpotential in the electrolyte containing one of the species of the redox couple (either V 4+ or V 5+ ) and not a solution of both.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…19 Recently, we reported the transport mechanism of redox species across the porous thin-lm electrode/electrolyte interface and explained the conditions in which either W s element or (R 2 , Q 2 ) elements should be used to t the nite transport feature. 30 Similar EIS features with equimolar concentration of V 4+ /V 5+ redox species at EP are reported in the literature. 29,41,42 However, several others have reported such features (one semi-circle and $45 line) by recording EIS even at measured OCP or at some nite overpotential in the electrolyte containing one of the species of the redox couple (either V 4+ or V 5+ ) and not a solution of both.…”
Section: Resultssupporting
confidence: 82%
“…The semi-innite linear mass-transport feature is usually tted with the Warburg element (W) and thus, the feature is also known as Warburg diffusion. [29][30][31] From the inset to Fig. 2, it is observed that the linear t to the LF data is at $45 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The general preparation procedure of such thin-film electrodes includes the addition of polymer binders to porous carbon to improve the mechanical integrity of the thin-film electrodes. 6–14 The transport and the subsequent adsorption of redox species into a porous carbon-modified electrode surface may include three consecutive steps. The first step is the advection or bulk transport of the ions to the hydrodynamic boundary layer surrounding the electrode/electrolyte interface.…”
Section: Introductionmentioning
confidence: 99%
“…Molasses wastewater is a kind of wastewater with high pollutant concentration, which is rich in sugars, proteins, amino acids, vitamins, and other organic matter. Molasses wastewater, which has high concentrations of COD and complex components, could cause serious environmental pollution in the ecosystem [40]. At present, the COD removal rate of the existing molasses wastewater treatment methods is generally not very high.…”
Section: Water Quality Analysismentioning
confidence: 99%